PELESTARIAN PENGELOLAAN LINGKUNGAN LAUT BERDASARKAN PERSPEKTIF KEADILAN LINGKUNGAN HIDUP DALAM MELINDUNGI MASYARAKAT PESISIR - Hamri, Andi Rosadi; Putra, Alif Arhanda (JURNAL AKTA YUDISIA, 2023)
AbstractThe ocean plays a significant role in a country's economy, and Indonesia, with acoastline of approximately 95,181 km, has great economic potential. This sizeplaces Indonesia as the second country with the longest coastline in the world,after Canada. The economic potential of the ocean is estimated at US$3 trillion -US$5 trillion per year, or around Rp36,000 trillion - Rp60,000 trillion. This doesnot include other potentials such as biotechnology, marine tourism, and thedevelopment of marine transportation. The current government considersIndonesia's maritime potential as its main focus, but must also pay attention tothe negative environmental impacts that can occur due to overexploitation. Lawin its function as the protection of human interests has a purpose. For humaninterests to be protected, the law must be implemented. The implementation ofthe law can be done either normally, peacefully, or occurs due to a violation ofthe law. In the event of a violation of the law, the law that is violated must beenforced. It is through this law enforcement that the law becomes a reality. Basedon Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesiaand the principle of environmental justice, all land and water and the naturalresources contained therein are controlled by the state and used for the greatestprosperity of the people. Every living system communicates with other livingsystems and shares resources that allow each living system to develop its ownidentity. All living beings are boundary creatures, but all living beings, includinghumans, are related and part of a system of interdependent relationships.Keywords: Conservation, justice, environment, community, coastal